Being harmed while doing good: affective injuries in a community development programme, Medan, Indonesia. (29th June 2018) - Jakimow, Tanya
Abstract: Complaints, accusations, and failures of gratitude are everyday experiences for volunteers in community‐driven development in Medan, Indonesia. In this article I develop the analytic of 'affective injury' to describe the force of such encounters: the sensation of having one's ethical self questioned or put at risk that manifests as an immediate force or lingering hurt. While humanitarian and development workers are all susceptible to affective injuries, I argue that they operate on a different register for developers who belong to, and have an enduring relationship with, the 'community'. The ways local volunteers respond to, and seek to recover from, affective injuries are distinct from reflective responses to ethical dilemmas. The suppression of, or diversion from, thoughts that could derail self‐understanding is a hindrance to reflexive development practice.